Nowa metoda wyznaczania krzywej naprężenie-odkształcenie przy ścinaniu - LITOŃSKI, Jacek (Engineering Transactions, 1971)
New method of determining of the stress-strain curve for shear A simple formula (Eq. 2.13), is derived which enables determination of the stress–strain curve for simple shear from the known distribution of the angle of the total shear on the lateral surface of the plastically twisted conical bar and measured final torque. This formula gives good results for materials whose τ (tg γ) diagram can be well fitted by a power type curve. For other materials the method gives approximate results. Certain possible applications of the above mentioned formula and its modifications are indicated.